Inhibition mechanisms of secretome proteins from Paenibacillus polymyxa Kp10 and Lactococcus lactis Gh1 against methicillin-resistant Staphylococcus aureus and vancomycin-resistant Enterococcus - Zainal Baharin, Nurul Hana; Khairil Mokhtar, Nur Fadhilah; Mohd Desa, Mohd Nasir; Dzaraly, Nurul Diana; Muthanna, Abdul Rahman; Yuswan, Mohd Hafis; Abbasiliasi, Sahar; Rahmad, Norasfaliza; Wan Nur Ismah, Wan Ahmad Kamil; Hashim, Amalia Mohd; Mustafa, Shuhaimi (Wolters Kluwer Medknow Publications, 2022)
Objective: To determine the inhibition mechanisms of secretome protein extracted from Paenibacillus polymyxa Kp10 (Kp10) and Lactococcus lactis Gh1 (Gh1) against methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococcus (VRE). Methods: The sensitivity and viability of MRSA and VRE treated with secretome proteins of Kp10 and Gh1 were determined using minimal inhibitory concentration, minimum bactericidal concentration, and time-to-kill assays. The morphological changes were observed using scanning electron microscopy and transmission electron microscopy. To elucidate the antimicrobial mechanism of secretome protein of Kp10 and Gh1 against MRSA and VRE, 2D gel proteomic analysis using liquid chromatography-mass spectrometry was run by comparing upregulated and downregulated proteins, and the proton motive force study including the efflux of ATP, pH gradient, and the membrane potential study were conducted. Results: MRSA and VRE were sensitive to Kp10 and Gh1 secretome protein extracts and displayed apparent morphological and internal composition changes. Several proteins associated with cellular component functions were either downregulated or upregulated in treated MRSA and VRE by changing the membrane potential gradient. Conclusions: Kp10 and Gh1 secretome proteins reduce the growth of VRE and MRSA by damaging the cell membrane. Cell division, cell wall biosynthesis, and protein synthesis are involved in the inhibition mechanism.